PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR INDUSTRI DASAR DAN KIMA DI BEI PERIODE 2013 – 2015 - Era Novita Sari, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2017)
This study aims to determine the effect of Good Corporate Governance onfinancial performance at basic and chemical industry manufacturing companies.Independent Variables Good Corporate Governance in this research is independentboard of commissioner, board of directors, audit committee, managerial ownership,and institutional ownership. The population in this study are all basic and chemicalmanufacturing companies listed on the Indonesia Stock Exchange (IDX) andcontinuously publish financial statements in 2013-2015. Based on purposivesampling method, samples obtained are 52 companies foreach yearin the period2013-2015, so obtain 156 observations data. As for the criteria of financialperformance in this study was measured by using Cash Flow Return on Assest(CFROA), whilst statistic analysis that used in this study was multiple linearregression with program Statistical Package for Social Science (SPSS) version 16.The result of this research showed that the variable of Good Corporate Governancethat is independent board and board of directors have positive influence to financialperformance in basic and chemical manufacturing company, while the variable ofGood Corporate Governance that is audit committee, managerial ownership, andinstitutional ownership have negative effect to financial performance at companyManufacturing basic industries and chemicals.Keywords: Good Corporate Governance, financial performance, CFROPENDAHULUAN